Polymerized small molecular acceptor based all-polymer solar cells with an efficiency of 16.16% via tuning polymer blend morphology by molecular design - Jiaqi Du (Nature Portfolio, 2021)
Through development of non-fullerene acceptors, OPVs have reached efficiencies of 18%, yet the inadequate operational lifetime still poses a challenge for the commercialisation. Here, the authors investigate the origin of instability of NFA solar cells, and propose some strategies to mitigate this issue.